Observing the Filipino family : a Filipino sociologist at work - Medina, Belen Tan-Gatue (Quezon City : UP Press, 2023)
No one in the Philippine social science community ha tracked the changing circumstances of the Filipino family more assiduously than retired University of the Philippines sociology professor Belen T.G, Medina
Part I. The Filipino Family in a time of rapid change -- Part II. Thee Formation of a Filipino Sociologist.
Keywords: FAMILIES -- PHILIPPINES -- HISTORY; MARRIAGE -- PHILIPPINES